Relationship between Body Image and Psychological Well-being in Patients with Morbid Obesity - Negar Yazdani; Sayed Vahid Hosseini; Masood Amini; Zahra Sobhani; Farkhondeh Sharif; Hajar Khazraei (Shiraz University of Medical Sciences, 2018)
Background: Morbid obesity is rising around the world. It can cause unpleasant appearance and body image. Most of the studies have aimed to evaluate the psychopathology of overweight and obesity and paying attention to mental well-being in morbid obese individuals is rare. Therefore, this study aimed to assess the relationship between body image and psychological well-being in morbid obese patients. Methods: This cross-sectional study, using simple random sampling method, was done on 124 morbid obese patients who referred to obesity clinic in Shiraz from 2016 to 2017. The data were collected by body image index and psychological well-being questionnaire. Results were analyzed using descriptive statistics, Pearson correlation coefficient test, ANOVA, and Regression analysis. Results: The results showed a significant relationship between body image and psychological well-being (r=0.43) (P<0.001), and between the total score of the body image and all the subscales of psychological well-being except autonomy and purpose in life (P<0.05). There was also a significant relationship between the total score of psychological well-being and all the subscales of body image (P<0.05). However, there was no significant difference between the mean scores of the body image and those of psychological well-being in different categories of body mass index (BMI) (P>0.05). Conclusion: Final results indicated that body image defects caused by obesity could lie in negative psychological well-being in all aspects. This study can promote health clinicians' knowledge in supporting of mental status of obese individuals. It is suggested that preventing and supporting intervention should be performed as effective methods for encountering and coping with psychological effects of obesity.